Board Chairman Characteristics and Performance of Islamic Banks: Evidence From Islamic Banks in Indonesia and Malaysia - Quddus, Ayatullah; Utama, Imron; Rosadi, Samsul; Rahmawati, Aryani (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2024)
Purpose: The purpose of this study is to explore the impact of chairman characteristics—specifically age, gender, and education level—on the performance of Islamic banks in Indonesia and Malaysia. The motivation for this research stems from the limited and mixed findings in existing literature regarding the role of leadership traits in shaping bank performance, especially in the context of Islamic banking. This research aims to fill the gap by analyzing how these specific characteristics influence the strategic decisions and overall performance of banks in these two countries, which are home to some of the largest Islamic banks globally. The key finding of this study is that while the age of the chairman significantly impacts performance, gender and education level do not show a notable effect. Methodology: The study employed a quantitative research methodology, using panel data from Islamic banks in Indonesia and Malaysia from 2015-2020. A panel data regression model was utilized to assess the influence of chairman characteristics on bank performance based on financial indicators such as return on assets (ROA). Data were collected from publicly available financial reports over a period of several years, and the characteristics of each chairman, such as age, gender, and education level, were analyzed in relation to these performance. Findings: The results of the regression analysis show that the age of the chairman has a significant positive relationship with bank performance. Older chairmen appear to contribute to better decision-making and long-term strategy formulation, which in turn improves the performance of Islamic banks. However, the gender and education level of the chairman were found to have no significant impact on the performance of these banks during the research period. This suggests that experience, reflected in age, plays a more crucial role than gender or educational background in determining bank performance. Novelty: This study provides valuable insights into the role of leadership chairman characteristics in Islamic banks, with a focus on the importance of age as a key predictor of bank performance. By contrasting the effect of age with gender and education, this research contributes to the ongoing debate about leadership in the financial sector. The novelty lies in its focus on the specific context of Islamic banks in Indonesia and Malaysia, offering a regional perspective on how leadership traits influence bank success. Future research could further explore additional leadership traits or examine a larger dataset across different regions to strengthen these findings.